Comparison of lipid profile parameters and oxidized low-density lipoprotein between normal and preeclamptic pregnancies in a tertiary care hospital in Nepal - Timalsina S; Gyawali P; Bhattarai A (Dove Medical Press, 2016)
Santosh Timalsina,1 Prajwal Gyawali,2 Aseem Bhattarai2 1Department of Biochemistry, Chitwan Medical College, Bharatpur, 2Department of Biochemistry, Maharajgunj Medical Campus, Maharajgunj, Kathmandu, Nepal Introduction: Preeclampsia is a pregnancy-specific complication that significantly contributes to maternal and perinatal morbidity and mortality worldwide, even more so in developing countries such as Nepal. The potential contribution of dyslipidemia and elevated levels of oxidized low-density lipoprotein (oxLDL) in the pathogenesis of preeclamptic pregnancies has been observed in several studies. The aim of this study was to compare the maternal lipid profile parameters and particularly oxLDL between preeclamptic and healthy pregnancies and also correlate oxLDL with other lipid profile parameters. Patients and methods: A total of 54 preeclamptic women were selected as cases for this cross-sectional study. Age and gestational week-matched 60 pregnant women were enrolled as controls. Preeclampsia was defined as per Australasian Society Consensus Statement research definition. The serum lipid parameters were measured using automated enzymatic systems and a competitive enzyme-linked immunosorbent assay was used to determine oxLDL concentrations in the serum. Student’s t-test was used to compare oxLDL levels between preeclamptic and healthy pregnancies, and Pearson’s correlation analysis was carried out to assess the relation between oxLDL and other variables. Results: The mean values of serum total cholesterol, triglyceride, non-high-density lipoprotein-cholesterol (non-HDL-c) and oxLDL were significantly higher in the preeclamptic cases (P<0.01). However, the levels of low-density lipoprotein cholesterol (LDL-c and HDL-c) did not significantly differ between the two groups. oxLDL had a significant positive correlation (P<0.01) with total cholesterol, triglyceride, LDL-c and non-HDL-c, and a negative correlation with HDL-c. Conclusion: The atherogenic type of dyslipidemia and high oxLDL levels are associated with preeclamptic pregnancies. The lipid parameters, however, seem to be poor markers of the severity of preeclampsia. Further prospective studies are needed to see if the observed dyslipidemia has a causal role in preeclampsia and imparts a long-term cardiovascular risk. Keywords: preeclampsia, oxLDL, dyslipidemia, Nepal